Evaluation of the influence of the posterior lingual frenulus in breastfeeding: clinical trial (Research, Society and Development, 2023)
Objective: To evaluate the influence of the posterior lingual frenulum on infant breastfeeding. Method: This is a longitudinal study, with a quali-quantitative, descriptive and analytical approach of the clinical trial type with a source of primary data. The studied population consisted of healthy mother-infant dyads, of both sexes, assisted at the Dental Specialties Center of the Instituto de Medicina Integral Prof. Fernando Figueira (IMIP), Recife, Pernambuco, from September to November 2022. Data collection took place from the assessment of the babies' lingual frenulum, as well as interviews with the mothers. The babies were divided into two groups for comparative purposes, namely the group of babies with posterior lingual frenulum of Coryllos type III (GIII) and the group of babies with posterior lingual frenulum of Coryllos type IV (GIV). Results: Coryllos type III posterior frenulum was found in 65.2% of babies, while type IV in 34.8%. Of these, 56.5% were exclusively breastfeeding in the first consultation and in the second consultation there was an increase to 73.9%. The prevalence of mothers who received guidance on the importance of breastfeeding during pregnancy was 52.2%. Conclusion: Both groups of babies with posterior lingual frenulum (GIII and GIV) presented difficulties in breastfeeding, with difficulty in latching on and breast pain during breastfeeding being more prevalent. After the initial consultation, given the exposure to guidelines, as well as the surgical procedure of lingual frenotomy, there was an improvement in the general condition of breastfeeding in almost all cases.